A phase 1 dose-sparing, randomized clinical trial of seasonal trivalent inactivated influenza vaccine combined with MAS-1, a novel water-in-oil adjuvant/delivery system. Issue 9 (23rd February 2022) - Gorse, Geoffrey J.; Grimes, Stephen; Buck, Helen; Mulla, Hussain; White, Peter; Hill, Heather; May, Jeanine; Frey, Sharon E.; Blackburn, Peter
Highlights: MAS-1 water-in-oil adjuvant with reduced doses of hemagglutinin (HA) was evaluated. HA + MAS-1 was safe and more immunogenic than standard dose unadjuvanted vaccine. Antibody responses were maintained up to 6 months with adjuvanted vaccine. Antibodies to some non-study vaccine strains were higher in adjuvanted vaccine groups. MAS-1 adjuvant offered HA dose-sparing effects and durable immunity in young adults. Abstract: Background: New influenza vaccines are needed to increase vaccine efficacy. Adjuvants may allow hemagglutinin (HA) dose-sparing with enhanced immunogenicity. MAS-1 is an investigational low viscosity, free-flowing, water-in-oil emulsion-based adjuvant/delivery system comprised of stable nanoglobular aqueous droplets. Methods: A phase 1, double-blind, safety and immunogenicity, HA dose escalation, randomized clinical trial was conducted. MAS-1 adjuvant with 1, 3, 5 or 9 µg per HA derived from licensed seasonal trivalent high dose inactivated influenza vaccine (IIV, Fluzone HD 60 µg per HA) in a 0.3 mL dose were compared to standard dose IIV (Fluzone SD, 15 µg per HA). Safety was measured by reactogenicity, adverse events, and clinical laboratory tests. Serum hemagglutination inhibition (HAI) antibody titers were measured for immunogenicity. Results: Seventy-two subjects, aged 18–47 years, received one dose of either 0.3 mL adjuvanted vaccine or SD IIV intramuscularly. Common injection site and systemic reactions post-vaccination were mild tenderness, induration, pain, headache, myalgia, malaise and fatigue. All reactions resolved within 14 days post-vaccination. Safety laboratory measures were not different between groups. Geometric mean antibody titers, geometric mean fold increases in antibody titer, seroconversion rates and seroprotection rates against vaccine strains were in general higher and of longer duration (day 85 and 169 visits) with MAS-1-adjuvanted IIV at all doses of HA compared with SD IIV. Adjuvanted vaccine induced higher antibody responses against a limited number of non-study vaccine influenza B and A/H3N2 viruses including ones from subsequent years. Conclusion: MAS-1 adjuvant in a 0.3 mL dose volume provided HA dose-sparing effects without safety concerns and induced higher HAI antibody and seroconversion responses through at least 6 months, demonstrating potential to provide greater vaccine efficacy throughout an influenza season in younger adults. In summary, MAS-1 may provide enhanced, more durable and broader protective immunity compared with non-adjuvanted SD IIV. Clinical Trial Registry: ClinicalTrials.gov # NCT02500680.